Water-gas shift assisted autothermal fuel reforming - Ding, Ovi Lian (2008)
A project has been carried out to investigate the behaviour of water-gas shift assisted autothermal reforming (ATR-WGS) utilising a 2-D heterogeneous kinetic model. The objective of this project is to study the behaviour of water-gas shift (WGS) assisted autothermal reforming (ATR) to enhance the concentration of hydrogen product without any external heat supply to the reformer. Cold start time for ATR-WGS reactor was found to be longer than ATR reactor due to the addition of a slower WGS process. It was also observed that WGS plays an important role in the final products of the reaction. In addition to these findings, the investigations in the transient performance of ATR-WGS showed that there are serious overshoot/undershoot of performance related parameters in the transients, whose values are quite different from those under steady state conditions.